Facile synthesis of mesoporous TiNb2O7/C microspheres as long-life and high-power anodes for lithium-ion batteries. (21st April 2020) - Yang, Yan; Yue, Yang; Wang, Lin; Cheng, Xinfeng; Hu, Yingtao; Yang, Zhi-zheng; Zhang, Ruixue; Jin, Bo; Sun, Ruixue
Abstract: The unique ReO3 crystallographic shear structure of TiNb2 O7 has enabled its application as anode material for lithium-ion batteries, in which the lattice parameter and volume change of TiNb2 O7 are often negligible during lithium-ion insertion/extraction. However, several intrinsic problems of TiNb2 O7, including low electronic and ionic conductivity, can restrict its application significantly. In this study, carbon-coated mesoporous TiNb2 O7 microspheres are fabricated through a simple solvothermal reaction. By combining the advantages of both the amorphous carbon and mesoporous structure, TiNb2 O7 /C composite exhibits superior lithium storage performance, with higher rate capability (200 mAh g −1  at 30 C) and cyclability (191 mAh g −1  at 10 C after 500 cycles). The improved performance is due mainly to the high pseudocapacitance and low charge transfer resistance obtained from the mesoporous structure and amorphous carbon layer. The study provides a new way of constructing TiNb2 O7 for ultra-fast storage devices, demonstrating great potential for application in power batteries. Highlights: TiNb2 O7 /C composite was successfully prepared by a simple solvothermal reaction. TiNb2 O7 /C composite exhibits higher rate capability and excellent cyclability. The higher performance is due to the mesoporous structure and carbon layer.